Women on probation and parole: a feminist critique of community programs & services - Morash, Merry (The Northeastern series on gender, crime and law, 2010)
Introduction : gender-responsive probation and parole -- Dominant crimes -- Women's characteristics by dominant crime subgroup -- Outcomes in the two counties -- Drug users who fail -- Supervision for women using drugs but not failing -- Positive changes for substance-centered women -- Keeping women off drugs -- Supervision for women without drug problems -- Conclusion : key findings and implications